2003
DOI: 10.1097/00042737-200304000-00012
|View full text |Cite
|
Sign up to set email alerts
|

A primary care cross-sectional study of undiagnosed adult coeliac disease

Abstract: This study describes the prevalence of undiagnosed adult coeliac disease in primary care patients with irritable bowel syndrome, iron deficiency anaemia and fatigue. Underdiagnosis of coeliac disease is common in primary care. A case-finding approach would avoid delays in diagnosis and the associated morbidity or potential complications of coeliac disease. A low threshold for serological screening of patients with coeliac-associated symptoms or conditions would be an optimal strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
154
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 230 publications
(165 citation statements)
references
References 29 publications
7
154
1
3
Order By: Relevance
“…[1][2][3] However, despite increased awareness, celiac disease remains under-diagnosed. A recent UK study demonstrated that only 1 in 4 patients with celiac disease are currently diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, despite increased awareness, celiac disease remains under-diagnosed. A recent UK study demonstrated that only 1 in 4 patients with celiac disease are currently diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom in 1950 the incidence of CD was reported as 1 in 8,000 ( 32 ). However, we and others including US investigators have reported in the last decade that CD aff ects up to 1 % of all adults ( 5,10 ).…”
Section: What Effect Has Gluten or Wheat Had On Mankind?mentioning
confidence: 70%
“…What is intriguing is that within this study Cash et al ( 23 )found that in their cohort of IBS patients, despite only 0.41 % being found to have CD, just over 7 % had CD-associated antibodies, predominantly IgG antigliadin antibodies (AGA) (4.88 % ) and IgA AGA (1.63 % ). Our group has previously reported that AGA were present in ~ 12 % of the general population and ~ 17 % in IBS (both in the presence of a normal small bowel biopsy) ( 10,14 ). Furthermore, Kaukinen et al ( 24 ) noted that the majority of patients with cereal induced (to gluten) on small bowel aspirate to defi ne an IBS subgroup ( n = 26).…”
Section: What Is the Relationship Between Ibs And Celiac Disease?mentioning
confidence: 90%
“…The etiology is not known, but environmental, immunological and genetic factors are held responsible for the condition. Celiac disease has been estimated to occur in up to 1% of the general population, and although was traditionally considered a childhood disease it may appear at any age, including the elderly (1)(2)(3)(4). Clinical presentations of the disease are highly variable.…”
mentioning
confidence: 99%
“…Though diarrhea and weight loss are usually present, in some patients manifestations of the disease may be protean. Moreover, some cases may present with only extra-intestinal symptoms without any obvious gastrointestinal changes (1,2). Neurological disorders, including peripheral neuropathy, ataxia, seizures and cognitive dysfunction have been reported in patients suffering from celiac disease; in some these disorders may be the initial manifestation of the disease, leading to its recognition (3-7).…”
mentioning
confidence: 99%